Case Report: Early acute kidney failure in an 11-year-old boy with Dent disease type 1 - Murphey, Nicolette; Authement, Craig; Hillman, Paul; Al-Akash, Samhar I.; Richardson, Kate (Frontiers in Pediatrics, 2024)
Dent disease type 1 (Dent 1) is a rare X-linked genetic condition which impacts kidney function and is caused by pathogenic variants in CLCN5. Affected males typically develop low molecular weight proteinuria, hypercalciuria, nephrocalcinosis, nephrolithiasis, and other symptoms. Kidney failure often occurs between the third to fifth decade of life. Here, we report an 11-year-old boy with Dent 1 and a severe kidney disease phenotype. The patient presented with flank pain, nocturnal enuresis, foamy urine, and increased urinary frequency. He was found to have nephrotic-range proteinuria, without hypoalbuminemia, and a significantly decreased estimated glomerular filtration rate at presentation. Further, he did not have hypercalciuria. His family history was remarkable for kidney disease among several relatives including a maternal half-brother and two sons of a maternal great aunt. Due to his symptoms and a strong family history, the patient underwent genetic testing that detected a novel pathogenic variant in CLCN5 [c.791dup (p.Ser265Glnfs*3)]. Given the variability of symptoms among family members and the early onset of severe symptoms in this young patient compared to prior literature, we encourage genetic testing for Dent disease in similarly affected individuals.